2006
DOI: 10.1111/j.1462-2920.2005.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of phosphonoacetate degradation and phnA genes in soil bacteria from distinct geographical origins suggest its possible biogenic origin

Abstract: Phosphonoacetate is regarded as an antiviral xenobiotic whose mineralization can be catalysed by an enzyme, phosphonoacetate hydrolase, encoded by the phnA gene. To date the enzyme's activity has been detected in only a limited number of bacteria. Its expression has been shown to occur in a manner independent of the phosphate status of the cell, in direct contrast to the general rule of organophosphonate metabolism being under the control of the pho regulon. In this study the environmental occurrence of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…Indeed, our Spearman rank correlation results indicated a significant correlation between Phi and 2-PA and between Phi and 2-AEP (see Tables S2 and S3 in the supplemental material) for CH soil and PA soil, while in sediments, we observed a strong correlation only between Phi and 2-AEP (see Tables S4 and S5 in the supplemental material). Our results support the idea that there is a connection between the use of phosphonates and phosphite, possibly explained by the relationship between the genes involved in phosphonate degradation and phosphite oxidation, as suggested in previous studies (65,68,69). However, a diversity of pathways is suggested from this study, as not all strains able to use Phi could use phosphonate; the sources of the Phi are enigmatic.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, our Spearman rank correlation results indicated a significant correlation between Phi and 2-PA and between Phi and 2-AEP (see Tables S2 and S3 in the supplemental material) for CH soil and PA soil, while in sediments, we observed a strong correlation only between Phi and 2-AEP (see Tables S4 and S5 in the supplemental material). Our results support the idea that there is a connection between the use of phosphonates and phosphite, possibly explained by the relationship between the genes involved in phosphonate degradation and phosphite oxidation, as suggested in previous studies (65,68,69). However, a diversity of pathways is suggested from this study, as not all strains able to use Phi could use phosphonate; the sources of the Phi are enigmatic.…”
Section: Discussionsupporting
confidence: 91%
“…Phosphonate degradation has been reported to occur via the phosphonatase pathway in marine bacteria (64), as well as in soil bacteria (65). This pathway is present in diverse bacteria, including representatives of Proteobacteria, Planctomycetes, Cyanobacteria (65), and Firmicutes (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that phnA is much more abundant than phnX throughout the water column, indicating that phosphonoacetate could be a natural product that is more abundant and ubiquitous than 2-AEP and its derivatives. The phnA gene also occurs in soil bacteria, suggesting that terrestrial bacteria could be a natural source of phosphonoacetate (Panas et al 2006). Phosphonates can be present in various biomolecules, including lipids, proteins and antibiotics (Kolowith et al 2001, Sannigrahi et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…The organic functional group would then be released as a by-product. Thus, consumption of LMW phosphonates may result in the release of soluble organic compounds that can be used as C or energy sources (32) or of gaseous compounds that may escape consumption, such as ethane or methane (15,33).…”
mentioning
confidence: 99%